Morphological and functional maturity of the oral jaws covary with offspring size in Trinidadian guppies - T. R. Dial (Nature Portfolio, 2017)
Abstract Large size of individual offspring is routinely selected for in highly competitive environments, such as in low-predation populations of the Trinidadian guppy (Poecilia reticulata). Large guppy offspring outcompete their smaller conspecifics, but the functional mechanisms underlying this advantage are unknown. We measured jaw kinematics during benthic feeding and cranial musculoskeletal morphologies in neonates and juveniles from five populations of Trinidadian guppy and found that both kinematics and morphologies vary substantially with neonatal size. Rotation at the intramandibular joint (IMJ), but not the quadratomandibular joint (QMJ), increases with size among guppy offspring, from 11.7° in the smallest neonates to 22.9° in the largest neonates. Ossification of the cranial skeleton varies from 20% in the smallest neonates to 90% in the largest. Relative to standard length (SL; jaw tip to caudal fin base distance), the surface area of jaw-closing musculature scales with positive allometry (SL2.72) indicating that muscle growth outpaces body growth. Maximum gape also scales with positive allometry (SL1.20), indicating that larger neonates are capable of greater jaw excursions. These findings indicate that size is not the sole adaptive benefit to producing larger offspring; maturation provides a potential functional mechanism underlying the competitive advantage of large offspring size among Trinidadian guppies.